Updated county-level distribution records for Wisconsin short-horned grasshoppers (Orthoptera, Acrididae and Romaleidae) - Mathew L. Brust; Charles Bomar; Alexander J. Harman (Journal of Orthoptera Research)
The last update to the Wisconsin county-level distribution records for Wisconsin short-horned grasshoppers (Orthoptera: Acrididae and Romaleidae) was in 2005. Since then, the first author has done periodic collecting and photography in Wisconsin and has acquired a significant number of new county records. In addition, new online resources such as BugGuide and iNaturalist have become useful and mostly reliable sources of data. Using this combination of sources, we have compiled 99 new county records, increasing the number of county records by at least 20% for the following species: Dendrotettix quercus (Packard) (9 to 14), Dichromorpha viridis (Scudder) (14 to 23), Melanoplus fasciatus (Walker) (11 to 17), Melanoplus scudderi (Uhler) (3 to 5), Melanoplus viridipes Scudder (23 to 33), Melanoplus walshii Scudder (20 to 27), Stethophyma lineata (Scudder) (3 to 4), and by over 50% for Melanoplus punctulatus (Scudder) (10 to 30). In addition, a species new to Wisconsin, Melanoplus gracilis (Bruner), was photographed in three counties between 2020 and 2024. These examples suggest that some grasshopper species are likely overlooked in the state, particularly those associated with woodlands.